The Effect of Counseling on Knowledge and Attitudes of Young Women About Dysmenorrhea at MTSN Model Palu: Pengaruh Penyuluhan Terhadap Pengetahuan dan Sikap Remaja Putri Tentang Dismenore di MTSN Model Palu - Widya Pani (Poltekkes Kemenkes Palu, 2022)
Background: Dysmenorrhea is a disorder that occurs during menstruation and often occurs in adolescent girls, causing feelings of anxiety and negative beliefs about menstrual pain, the incidence of dysmenorrhea in adolescents with a prevalence of 43% to 93%. Purpose: Effect of counseling on knowledge and attitudes of adolescents daughter about dysmenorrhea at MTsN model Palu. Methods: This type of analytic research with a pre-experimental design the one group pretest-posttest design. The total population of this study were all students of class VII and VIII of MTSN Palu Model as many as 309, the sample size used the slovin formula, the sample size was 76 respondents, and the sampling technique used proportional stratified random sampling. The sample was taken by lottery technique. The analysis used the Wilcoxon test through a computerized system. Results: There was an increase in knowledge of 69.7% and an increase in attitude of 63.5% after being given counseling. Statistical test has the effect of counseling on increasing knowledge and attitudes of young women about dysmenorrhea (r = 0.000 < α =0.05). Conclusion: Counseling affects the knowledge and attitudes of young women about dysmenorrhea at MTsN Model Palu. Suggestions need to do research with different variables.